Complex consequences of conservation success: Emerging human-tiger conflicts in Nepal - Fitzmaurice, A; Poudel, P; Offord-Woolley, S; Macdonald, D; Thapa, S; Lamichhane, BR; Baral, A; Yadav, BP (IUCN/SSC Cat Specialist Group, 2021)
Between 1910 and 2010, range-wide tiger populations plummeted from around 100,000 to an estimated 3,200. Poaching, habitat destruction and human-wildlife conflict have all contributed to this dramatic decrease. In Nepal, the Bardia-Banke Complex, consisting of Bardia National Park (BNP) and Banke National Park (BaNP) and their buffer-zones, is a critical habitat to the Bengal tiger Panthera tigris. Conservation efforts in recent decades have contributed to increasing the tiger population. Despite this increase, no human fatalities associated with human-tiger conflict were reported in the decade prior to 2019: a crucial feature of conservation success. In 2019, ten reported human-tiger incidents resulted in seven human fatalities, three people badly injured, and one tiger taken into captivity. The question of why conflicts involving humans and tigers have suddenly increased requires urgent answers to inform future policy. The development and implementation of case-specific coexistence strategies is a prerequisite to the conservation of this iconic species. This paper explores the complex unintended consequences of conservation success and critically evaluates the circumstances that may explain this recent surge in human deaths and injuries.